Pedagogical-Psychological Aspects Of Teaching Elementary Particle Physics In Practical Classes In General Physics - Madaliyev Akmaljon Makhammadjonovich (Euro Asian Journal Publishing, 2023)
In this article, the pedagogical and psychological aspects of solving problems related to the physics of elementary particles in practical classes from general physics are considered
Keywords: student; reader; psychology; psyche